Fertilizer Recommendation for Strawberry under Adtuyon Clay Loam Soil: Mitscherlich Bray Equation Approach - Jambaro, Gerlie S.; Ozarraga, Louell M.; Escomen, Edgel O. (Research Highlights in Agricultural Sciences Vol. 3, 2022)
Strawberry fertilization is critical requirement to be productive under Adtuyon clay loam. This soil is characterized by inherent low soil fertilizer hence liming and fertilization is required. The Mitscherlich-Bray equation was used in this investigation to calculate the theoretical maximal yield and compare it to the actual yield. When determining the fertiliser recommendation, the economics of fertiliser application were also taken into account. The theoretical maximum yield of the study is 12.29 t/ha-1. Strawberry is found responsive to nitrogen and potassium fertilization. The application of 225-225-360 kg ha-1 of N, P2O5, and K2O, respectively, could provide 95% of the theoretical maximum yield, however the fertilisation costs per kilogramme of fruit production were substantially greater than those suggested by the present Hafza. The fertiliser recommendation of 150-150-240 kg ha-1 of N, P2O5, and K2O, respectively, remains the optimum option for both economic and horticultural benefits under Adtuyon clay loam.